Pengaruh Beban Kerja Dan Stres Kerja Terhadap Burnout Pegawai Di Rumah Sakit Bhayangkara Makassar Tahun 2024 - Mangindara Mangin; Sriyani Windarti; Dian Ekawaty; Hastuti Hastuti; Rival Hardiansyah (Wal'afiat Hospital Journal, 2025)
Burnout Syndrome refers to a condition in which the body is completely exhausted, both physically and mentally. According to data from the International Labour Organization (ILO) in 2021, nearly 2 million workers die each year due to work-related accidents caused by fatigue. Of these, 71.43% of workers experienced mild fatigue before starting work. After work, 100% of workers experienced fatigue, with 11.43% reporting mild fatigue, 42.86% moderate fatigue, and 45.71% severe fatigue. It is noted that the number of contract employees at Bhayangkara Hospital Makassar is 448, with 7 employees having resigned, which accounts for 1.52%. The aim of this study is to determine the effect of workload and work stress on employee Burnout at Bhayangkara Hospital Makassar in the year 2024. This study used a quantitative research method with a cross-sectional study design. The total population in this study was 448 individuals, with a sample of 211 respondents. Data collection was conducted using questionnaires, and the analysis techniques included univariate, bivariate, and multivariate analysis. The results showed that workload had a significant effect on Burnout (p = 0.000), work stress had a significant effect on Burnout (p = 0.000), and there was a simultaneous effect of workload and work stress on Burnout, where the calculated F-value (7.363) was greater than the F-table value (3.04), with a significance value of 0.000 < 0.05.Conclusion: There is a simultaneous effect of workload and work stress on employee Burnout at Bhayangkara Hospital Makassar.